What Does Aristotle's Craftsperson Understand? - Kietzmann, Christian (Archiv für Geschichte der Philosophie, 2023)
I argue for the claim that for Aristotle, the content of productive understanding primarily concerns the nature of the object a craftsperson aims to bring into existence as well as its material requirements, and only derivatively things she might do with a view to producing that object. I explain why technê is a form of understanding, by considering what it shares with and how it differs from its practical and theoretical cousins. I give four arguments for my claim. The analogy of craft and nature suggests that a craftsperson understands the nature of their product and the material necessities required by the product's existence. Further evidence comes from some of Aristotle's remarks on the practical syllogism, from considerations concerning capacities for change in general, and from his views on why it is a two-way capacity. I end by mentioning several respects in which technê goes beyond productive understanding.
CRIS-Team Scopus Importer:2023-11-10